2017
DOI: 10.1186/s12879-017-2330-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced liver injury from antituberculous treatment: a retrospective study from a large TB centre in the UK

Abstract: BackgroundWe describe drug-induced liver injury (DILI) secondary to antituberculous treatment (ATT) in a large tuberculosis (TB) centre in London; we identify the proportion who had risk factors for DILI and the timing and outcome of DILI.MethodsWe identified consecutive patients who developed DILI whilst on treatment for active TB; patients with active TB without DILI were selected as controls. Comprehensive demographic and clinical data, management and outcome were recorded.ResultsThere were 105 (6.9%) cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
62
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 37 publications
(41 reference statements)
10
62
3
3
Order By: Relevance
“…Case fatality rates (CFR) for other sub-population are presented in Supplementary Table 2 [28,29], its clinical implication in increasing the risk of mortality should be taken seriously. Two studies from India and the UK also reported DILI as a contributing cause of death in adult TB patients [30,31], with the risk of mortality being even higher if accompanied by jaundice, ascites or encephalopathy [31]. Based on the current WHO guidelines for children, regular monitoring of liver function tests (LFTs) during TB-therapy is not mandatory and only recommended if liver tenderness, hepatomegaly, jaundice or early onset of vomiting occur during treatment [32].…”
Section: Resultsmentioning
confidence: 99%
“…Case fatality rates (CFR) for other sub-population are presented in Supplementary Table 2 [28,29], its clinical implication in increasing the risk of mortality should be taken seriously. Two studies from India and the UK also reported DILI as a contributing cause of death in adult TB patients [30,31], with the risk of mortality being even higher if accompanied by jaundice, ascites or encephalopathy [31]. Based on the current WHO guidelines for children, regular monitoring of liver function tests (LFTs) during TB-therapy is not mandatory and only recommended if liver tenderness, hepatomegaly, jaundice or early onset of vomiting occur during treatment [32].…”
Section: Resultsmentioning
confidence: 99%
“…[9] From the patients who developed drug induced liver injury almost 50% of patients develop due to the antitubercular therapy, Hence ATT should be considered for universal liver monitoring particularly during the first 8 weeks of treatment. [10] Further similar study may clearly suggest the importance of routine test of liver function test of the patient on ATT.…”
Section: Discussionmentioning
confidence: 99%
“…Various other studies have shown the incidence of hepatoxicity ranging from 6.9% -8.7%. 26,27 CONCLUSION TB poses a significant threat to global health still today, causing the second highest mortality rates from an infectious disease worldwide, after HIV/AIDS. In this study, an analysis of 54 patients was done who were diagnosed to have Disseminated TB and HIV co-infection.…”
Section: Discussionmentioning
confidence: 99%